Novel mRNA-Engineered Fully Human CAR-T Cells Targeting AXL in Solid Tumors - Bo Zou; Mengge Wang; Shimeng Bai; Ning Li; Zhongyi Fan; Yuanzheng Peng; Mingshu Han; Chen Zeng; Hongzhou Lu; Lin Qi; Xingding Zhang; Xiaohua Tan; et al. (Biomedicines)
Background/Objectives: The AXL receptor tyrosine kinase is a promising therapeutic target in solid tumors, yet conventional viral vector-engineered CAR-T cells face critical limitations, including risks of insertional mutagenesis and immunogenicity from murine-derived single-chain variable fragments (scFvs). This study aimed to develop and evaluate mRNA-engineered fully human AXL CAR-T (mfhAXL CAR-T) cells as a safer, scalable alternative for solid tumor immunotherapy. Methods:mfhAXL CAR-T cells were generated via electroporation-mediated delivery of in vitro transcribed mRNA encoding a fully human AXL-specific CAR. CAR expression kinetics and T-cell viability were quantified by flow cytometry. Antitumor activity was assessed through in vitro co-cultures with AXL-positive lung and pancreatic cancer cells, measuring cytotoxicity, cytokine secretion, and specificity. In vivo efficacy was evaluated in a lung cancer xenograft mouse model, with tumor volume and body weight monitored over 14 days. Results: Flow cytometry confirmed transient but high CAR expression (>90% at 24 h) with preserved T-cell viability (>90%). In vitro, mfhAXL CAR-T cells exhibited dose-dependent cytotoxicity and antigen-specific cytokine secretion. In vivo, four administrations of mfhAXL CAR-T cells suppressed tumor growth without body weight loss. Conclusions: The mRNA-electroporated mfhAXL CAR-T platform enables cost-effective, large-scale production, offering a safer alternative to viral vector-based approaches by eliminating risks of insertional mutagenesis and immunogenicity.